"All The World's A Stage": Takarazuka Revue And Its Theatralisation Of Culture(S) - Grajdian, Maria (Penerbit Universiti Sains Malaysia (USM Press), 2014)
Founded in 1913 by Kobayashi Ichizō, one of the most significant entrepreneurs in prewar Japan, Takarazuka Revue proved itself along its centennial existence both a faithful mirror of and an influential model for the Japanese society. Simultaneously conservative in its gender representation and progressive in its performance practice, a contradictory symbol of the Japanese modernity and Japan's leading figure in entertainment industry, emerged from the syncretic, cross-gender tradition of the centuries-old classical Japanese stage arts and challenging that very tradition through the creative employment of Western music and dramatic plots, Takarazuka Revue reconstructs in a specific way asymmetric interactions between identity and alterity, model and copy, history and geography, obtrusively displayed in sparkling tunes, fairy-tale-like sceneries and gorgeous costumes. While taking into account the multiple layers in Takarazuka Revue's administration and self-orchestration such as performance politics, the economical supervision of brand-related consumption, the socio-cultural management of actresses and fandom (fans and fan communities) as well as the performances itself, this paper focuses on some of Takarazuka Revue's strategies to construct cultures—indigenous as well as alien—by means of theatrical reproduction. Especially the last 20 years—since the opening of the Grand Theater in Takarazuka in 1993—marked an unexpected tendency in Takarazuka Revue's public appearance, visible, on one hand, in the increasing lavishness of its performances and the intensified commercialisation of the increasingly androgynous otokoyaku figures, and on the other hand, in the highlighting of individuals, societies and empires as key entities in structuring the dramaturgic flow. This paper's aim is, thus, to analyse Takarazuka Revue's position as cultural institution within the Japanese late modernity, possibly carrying deep-going and wide-reaching messages of a new identity paradigm based of "love" in its body as a local mass medium.